2016
DOI: 10.1371/journal.pone.0168155
|View full text |Cite
|
Sign up to set email alerts
|

CD5-CK2 Signaling Modulates Erk Activation and Thymocyte Survival

Abstract: CD5 is well recognized for its importance in thymic selection. Although this property of CD5 has been attributed to its ITIM-domain dependent regulation of TCR-signal strength, the mechanism has not been established. A second major signaling domain within the cytoplasmic tail of CD5 is a CK2 binding/activation domain (CD5-CK2BD). Using a gene-targeted mouse in which the CD5-CK2BD is selectively ablated (CD5-ΔCK2BD), we determined that loss of function of CD5-CK2 signaling in a MHC-II selecting TCR transgenic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Interestingly, these IL‐23R induction does not seem to be dependent of the CD5‐CK2 mediated signaling suggesting alternative pathways through which CD5 can regulate IL‐17/Th17 generation. Regarding the role of the CK2‐binding domain of CD5 in Treg generation, it was reported that the absence of this domain did not affect tTreg generation; however, unpublished data from our group (Burgueño‐Bucio et al., in preparation) suggest that this domain does have an impact in iTreg generation.…”
Section: Cd5 As Regulator Of Th Differentiationmentioning
confidence: 70%
See 3 more Smart Citations
“…Interestingly, these IL‐23R induction does not seem to be dependent of the CD5‐CK2 mediated signaling suggesting alternative pathways through which CD5 can regulate IL‐17/Th17 generation. Regarding the role of the CK2‐binding domain of CD5 in Treg generation, it was reported that the absence of this domain did not affect tTreg generation; however, unpublished data from our group (Burgueño‐Bucio et al., in preparation) suggest that this domain does have an impact in iTreg generation.…”
Section: Cd5 As Regulator Of Th Differentiationmentioning
confidence: 70%
“…61 By using CD5-deficient mice, it was demonstrated that thymi development. 63 This experiment showed that the inability of CD5 to bind CK2 during thymic development results in an increased generation of CD4+ T cells at the expense of a reduced number of DP cells. This shift in the thymic subpopulations is the result of at least two combined effects: First, the absence of the CD5-CK2 binding region results in an increased apoptosis of DP cells, although it also affects CD4+ T cells and CD8+ T cells; and second, the absence of this domain increased pERK levels which results in altered negative and positive selection processes.…”
Section: Role Of Cd5 In Thymocyte Survivalmentioning
confidence: 91%
See 2 more Smart Citations
“…ERK2 regulates CD8 + T cell proliferation and survival . ERK phosphorylation can be elevated in the absence of CD5‐CK2 signalling . To determine if administration of anti‐CD5 MAb could lead to impaired CD5 signalling and increased ERK activation, splenocytes isolated from tumour‐naïve mice and treated with anti‐CD3 plus anti‐CD5 MAbs showed increased phosphorylation of ERK1/2, but not cells receiving anti‐CD3 MAb alone (Fig.…”
Section: Resultsmentioning
confidence: 99%